An Analysis of Interactive Metadiscourse Markers in the Original Novel "The Scarlet Letter": تحليل ادوات الخطاب الشارح التوجيهي في الرواية الاصلية "الحرف القرمزي" - حاكم حمد المالكي, زيد; رائد داخل كريم الخزاعي (Journal of College of Education, 2023)
Academic writers employs the term "metadiscourse" in their writings to convince their audience by leading and engaging them in the text through both levels of metadiscourse, that is, interactive and interactional levels. The current study strives to investigate the interactive level of metadiscourse markers in the original novel "The Scarlet Letter". Furthermore, ten samples are selected as data to be analysed. The study aims to investigate the frequencies and function of each marker in interactive metadiscourse. To achieve the aims, three hypotheses are utilized: First, the interactive metadiscourse markers have an essential impact on audience guide through the text. Second, the writer guides his/her readers in the text, using a higher frequency of transition markers. Third, endophoric and evidential markers are not significantly used in literary genres. To prove the hypotheses, the study includes the following procedure: A literature review is presented, and the first level of Hyland's (2019) metadiscourse model is adopted. Data are selected and analysed using qualitative and quantitative approaches, and finally the study reveals and discusses the findings. Ultimately, the results reveal that interactive metadiscourse markers are significant in forming cohesive and coherence text, especially transition markers which are dominantly employed. In addition, endophoric markers and evidential markers are not employed since these markers are not used in the literary genre. Nevertheless, they are used frequently in academic and scientific disciplines.
Keywords: : metadiscourse, original novel, interactive metadiscourse, The Scarlet Letter